Developing 3D Printed Hexagon Tiles from Recycled Plastic Bottles for Sustainable Construction - Zainal, Nur Najwa; Raja Muhammad Putra, Raja Muhammad Farishilmi; Aminudin, Zureen Aleya; Mohammad Azmi, Mohamad Azim; Muhamad Fadzir, Muhammad Amirulhusni (Multidisciplinary Applied Research and Innovation, 2026)
This project explores the potential of transforming plastic waste into sustainable construction materials through the production of 3D printer filament and hexagonal tiles. With the construction industry heavily reliant on conventional materials, this approach addresses critical environmental challenges, including pollution, resource depletion, and the underutilization of plastic waste. The process begins with collecting and preparing 30 kg of plastic bottle caps by cleaning, drying, and shredding them into smaller pieces. These shreds are melted and extruded into uniform filaments, which are then spooled and stored under controlled conditions to maintain quality. The filament is utilized in 3D printing to create hexagonal modular tiles with interlocking designs. Hexagons were chosen for their efficient space usage, structural stability, and seamless fitting, which reduce material waste and enhance durability. The tiles were evaluated for mechanical properties, including Shore D hardness and tensile strength, as well as impact resistance. Additionally, the interlocking feature simplifies installation and improves structural integrity. Results confirm the feasibility of using recycled plastic tiles in construction applications, offering an eco friendly alternative to traditional materials. This study demonstrates a practical, sustainable approach to repurposing plastic waste while promoting innovation in modular construction. By integrating 3D printing technology, efficient design principles, and recycling techniques, the project highlights the potential for greener practices in the building sector. The findings emphasize the importance of combining waste management, advanced manufacturing, and innovative designs to reduce environmental impacts, promote circular economies, and foster sustainable development in construction.